A study on international trend and Korean measures regarding Cape Town Agreement of 2012. (3rd July 2022) - Hwang, Dae-Jung
ABSTRACT: At the global level, regulations on the safety of ships are gradually strengthening. Comparing international regulations on the safety of merchant vessels and fishing vessels, fishing vessels did not have a relatively strong safety regulations compared to merchant vessels. However, the importance of fishing vessel safety is being emphasized internationally for various reasons, such as the increase in IUU fishing activities. The Cape Town Agreement of 2012 is a representative international convention on the safety of fishing vessels. Although it has not yet met the requirements for entry into force, but several member states, including the IMO Secretariat, continue to encourage the entry into force of the Agreement. For reference, the Republic of Korea is also preparing various fishery policies with the goal of ratifying the agreement in 2023. This paper briefly introduces international trends related to the ratification of the Cape Town Agreement. In addition, by reviewing the current status of preparations of the Republic of Korea for ratification of the agreement in general, essential preparation measures for smooth ratification and implementation of the Cape Town Agreement have been identified.